(3eNJUQ GdeYJeO aj CUhd Gdabgs - (3SdjeGf Hf fGUQ Hf SYjOs; (3eMeO Hf Ydj GdWjH GdHUQj, CHh GdMSjf,J (B436 (3g` s ((3SdjeGf Hf GdeXaQ Hf YjSi Hf eMeO s)
(3ChdgG (B:s
(3CYde Cf GdZQV HPdc gh Gdbhd ai Cf GdELeGY MLI s
(3BNQgG (B:s
(3Jcdja GdjghO hGdfUGQi hGdedMOI hGdEKHGJ hgPG eLGd s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B275s
Keywords: (3CUhd Gdabgs